(untitled) (Journal of Interdisciplinary Insights, 2024)
This study examines the implementation of the Arts (Music Education) core curriculum in Mongolia’s primary and secondary education system under the framework of "Child-Development-Music-Progress." Surveys were conducted among students, experts, administrators, and music teachers to assess the curriculum’s effectiveness. The research involved 3200 high school students, 354 professionals, and teachers. Based on the findings, a new curriculum model for music education for Grades 1–9 in general education schools is proposed. This model emphasizes national content while incorporating international trends to promote child development through music education.